DEVELOPMENT OF EXECUTIVE FUNCTIONS FOR EARLY CHILDHOOD IN NAKHON SI THAMMARAT BORDER PETROL POLICE SCHOOL WITH TOYS MADE FROM LOCAL MATERIALS - Chitkla, Suchada; Jeh-Uma, Suda; Sutra, Julalax; Navarat, Janjira (Journal of MCU Nakhondhat, 2025)
The objectives of this research paper were 1) To study the Ban Khao Wang community in terms of ecology, history, and local wisdom, 2) To develop an EF brain skills curriculum using toys from local materials, and 3) To develop an EF brain skills curriculum using toys from local materials. Create a learning network that is appropriate for the child's development and the context of the community. The sample group is as follows: 8 villagers 3 community leaders, 3 village sages and 12 early childhood children. Selected by a specific method (Purposive Sampling) and voluntarily participated in the activity. Research tools include questionnaires, in-depth interviews, workshop materials, satisfaction assessments, and other materials. The data collection is divided into 3 phases: 1) Basic Data Study, 2) Curriculum Development, and 3) Curriculum Development. Evaluation of curriculum development using basic statistics to analyze data such as mean ( ) and standard deviation (S.D.) The results showed that: 1) The Ban Khao Wang community has outstanding ecological characteristics such as important watersheds, streams, and natural resources that are conducive to traditional living. The community still maintains local wisdom through the use of natural materials in their livelihoods. 2) The EF Brain Skills Course for Early Childhood consists of a good food unit, our community, loves Thailand, toys, and fun with numbers, and 3) the curriculum evaluation shows that the overall average ( = 2.58), basic skills ( = 2.65) and self-directed skills ( = 2.50) are at a high level, reflecting the suitability of the curriculum in developing EF brain skills of early childhood in the context of the Ban Khao Wang community effectively. Additionally, the establishment of a learning network strengthens the community and promotes the exchange of knowledge between community members and researchers.